PENGIDENTIFIKASIAN ENTALPI BAHAN BAKAR PADAT (CHAR) DAN CAIR (TAR) HASIL PROSES PIROLISIS BIOMASA - Widya Wijayanti (ROTOR, 2014)
An experimental study of pyrolysis method had been conducted to support alternative fuels demand. It was very attractive method to convert the biomass; mahogany wood to be the alternative fuels. For that reason, an appropriate pyrolyzer will be required to support the process. Due to thermochemical process, an occurred energy transfer all through the process considered not only the heat transfer mechanism but also the chemical reaction mechanism producing heat of reaction in the pyrolysis products (enthalpy). Therefore, the study aims to identify the influence of different temperatures on the measured enthalpy of pyrolysis by means of calorimetrical measurement. The biomass samples used mahogany wood that would be pyrolyzed in the experimental run. Afterward, the influence of temperature toward the solid (char) and liquid (tar) yields were investigated. The enthalpy yields formation would be presented by calorific/heating value of formed char/solid yields indicating important-physical properties of fuel. The results referred that the values of solid yield enthalpy were pointed in the increasing values with the increasing of pyrolysis temperature, however,the enthalpy values of tar inclined to temperature of 500°C. It would decline because the viscosity of tar becomes lighter. Keywords: Enthalpy, Char, Tar, Biomass, Pyrolysis